The Implications of the International Criminal Court Rulings on African Leaders: A Critical Assessment - Hassan, Ndaliman Alhaji; Saleh, Zahradeen Mallam; Sani , Safwan Mikaila; Sowore, Olatunji Julius (Kashere Journal of Politics and International Relations, 2023)
The International Criminal Court (ICC) was established to deal with the unabated global cases of war crimes and crimes against humanity, and to deter intending war lords and authoritarian leaders. The activities of the court have increasingly been beamed on Africa because of the incessant conflicts pervading the continent with accompanying violation of human rights. The unnecessary search light on Africa raises questions of selective treatment by the court and the need to ensure equity in its global coverage of crimes against humanity. The paper utilized secondary data and qualitative analysis as its methodology. The paper is premised on Finnis (1980) Interest Theory of Human Rights. The theory argued that citizens within a given state have rights that should be preserved and protected by the state. The rights of the citizens such as freedom of speech, security, assembly, association and self-determination are their interest which the state should not violate. The paper found that African leaders have become the major source of intimidation and degradation by the court, while leaders in the Middle East and Europe are left scot-free. The paper recommends that African countries should collectively pull out of the signatory to the court as a protest to the bullying of the continent.